Perfil epidemiológico e sociodemográfico de gestantes de alto risco no contexto amazônico - (:unkn) unknown (ISB - Instituto de Saúde e Biotecnologia (Coari), 2025)
Introduction: High-risk pregnancy refers to gestations with an increased likelihood of complications for the mother, fetus, or newborn compared to the general obstetric population. This condition results from the interaction of clinical, obstetric, gynecological, reproductive, and social factors, which may occur alone or in combination, heightening the probability of adverse outcomes. Objective: To analyze the epidemiological and sociodemographic profile of high-risk pregnant women in the Amazonian context. Method: This is a descriptive and cross-sectional study with a quantitative approach, conducted at the Dr. Roque Juan Delloso Polyclinic in the municipality of Coari, Amazonas. The study population consisted of 60 pregnant women receiving high-risk prenatal care. Data collection took place between July and October 2025 through a structured form based on instruments from the Brazilian Ministry of Health, including sociodemographic, economic, gynecological, obstetric, and current pregnancy variables. Ethical procedures followed Resolution No. 466/2012, approved by the Research Ethics Committee of the Federal University of Amazonas, with informed consent obtained from all participants. Data were analyzed using descriptive statistics with absolute and relative frequencies, tabulated in SPSS, and presented through tables and charts in Microsoft Excel 2019. Results: Most participants were between 25 and 31 years old (38.33%), self-identified as mixed race (80%), had completed high school (46.66%), lived in stable unions (56.67%), and resided in urban areas (75%). Families earned up to one minimum wage (76.67%), with social benefits as their main source of income (36.67%). Most women were multiparous (71.67%), had previous vaginal deliveries (46.67%), and a history of miscarriage (31.66%). Pregnancies were mostly single (93.33%), with prenatal care initiated between 6 and 9 weeks (63.33%), and obesity present in part of the group (38.33%). The most frequent complications were urinary tract infection (70%) and anemia (38.33%). The main reasons for referral to high-risk prenatal care included gestational diabetes (16.67%), maternal age of 35 years or older (15%), unfavorable reproductive history (10%), gynecological diseases (10%), and pre-existing conditions (8.33%). Conclusion: High-risk pregnant women in the Amazonian context are predominantly young, mixed-race, multiparous women with complete secondary education, low income, and social vulnerability. Despite good adherence to prenatal care, conditions such as obesity, gestational diabetes, and advanced maternal age increase pregnancy risks. The study also highlights gaps in communication and record keeping, indicating the need to improve prenatal care quality and information management
Keywords: Gestantes; Complicações na gravidez; Gravidez de alto risco; CIENCIAS DA SAUDE: ENFERMAGEM